Non-linear relationship between maternal work hours and child body weight: Evidence from the Western Australian Pregnancy Cohort (Raine) Study - Jianghong Li; Plamen Akaliyski; Jakob Schäfer; Garth Kendall; Wendy H. Oddy; Fiona Stanley; Lyndall Strazdins (Social Science & Medicine, 2017)
Using longitudinal data from the Western Australia Pregnancy Cohort (Raine) Study and both random-effects and fixed-effects models, this study examined the connection between maternal work hours and child overweight or obesity. Following children in two-parent families from early childhood to early adolescence, multivariate analyses revealed a non-linear and developmentally dynamic relationship. Among preschool children (ages 2 to 5), we found lower likelihood of child overweight and obesity when mothers worked 24 h or less per week, compared to when mothers worked 35 or more hours. This effect was stronger in low-to-medium income families. For older children (ages 8 to 14), compared to working 35–40 h a week, working shorter hours (1–24, 25–34) or longer hours (41 or more) was both associated with increases in child overweight and obesity. These non-linear effects were more pronounced in low-to-medium income families, particularly when fathers also worked long hours.
Keywords: 330; maternal work hours; fathers' work hours; child BMI; overweight; obesity; family income; the Raine Study